THE IMPORTANCE OF INTERCULTURAL COMMUNICATION IN THE ORIGIN OF MILITARY TERMINOLOGY - Aminova, Dilnoza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Studying the field of terminology is one of the most urgent problems in modern linguistics of the new century. To this day, many linguists are studying the terms of all fields and working hard to apply them to science. This article examines the origin of military terms in the English language in a diachronic aspect. The author spoke about the influence of extralinguistic and introlinguistic factors on the development of military vocabulary in English.